Urban birds' tolerance towards humans was largely unaffected by COVID-19 shutdown-induced variation in human presence - Mikula, Peter; Bulla, Martin; Blumstein, Daniel T; Benedetti, Yanina; Floigl, Kristina; Jokimäki, Jukka; Kaisanlahti-Jokimäki, Marja-Liisa; Markó, Gábor; Morelli, Federico; Møller, Anders Pape; Siretckaia, Anastasiia; Szakony, Sára; et al. (Communications biology, 2024)
The coronavirus disease 2019 (COVID-19) pandemic and respective shutdowns dramatically altered human activities, potentially changing human pressures on urban-dwelling animals. Here, we use such COVID-19-induced variation in human presence to evaluate, across multiple temporal scales, how urban birds from five countries changed their tolerance towards humans, measured as escape distance. We collected 6369 escape responses for 147 species and found that human numbers in parks at a given hour, day, week or year (before and during shutdowns) had a little effect on birds' escape distances. All effects centered around zero, except for the actual human numbers during escape trial (hourly scale) that correlated negatively, albeit weakly, with escape distance. The results were similar across countries and most species. Our results highlight the resilience of birds to changes in human numbers on multiple temporal scales, the complexities of linking animal fear responses to human behavior, and the challenge of quantifying both simultaneously in situ.
Keywords: strach; úniková reakce; COVID-19; Pandemics; zvířata; Humans; Fear; Birds; ptáci; pandemie; Escape Reaction; Cities; lidé; SARS-CoV-2; velkoměsta; Animals